Host-Community Readiness Towards Tourism Reactivity: Young People's Perspectives in Greater Bandung - Rosadi, Asep; Susanto, Eko; Fitriani, Tiara; Dewi, Aprilia Nurmala; Cantika, Wa Ode Ananda Yayang; Puluhulawa, Rosemery Pauline Rumayar (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2022)
Tourism during the pandemic became an actual study topic, the majority of which were studied in terms of changes in tourist behaviour. Plethora studies changes in tourist behaviour selfishly view tourism for the benefit of tourists alone. In contrast, this study examines the readiness factors of community hosts in receiving visits and plays a role in the tourism value chain during the pandemic. Using 310 young respondents living in Indonesia's urban tourism destinations (Greater Bandung), the study confirmed the perceptual factors forming host community readiness. Using SEM-PLS, the study has found that perceptions of internal conditions by the community have a significant impact on the perception of tourism reactivation and the readiness of community hosts. The research model has been able to moderately predict the readiness of community hosts in tourism during the pandemic. Several recommendations were submitted in this study for tourism stakeholders to prepare community hosts in their efforts to achieve successful tourism reactivation.